2019
DOI: 10.1002/adfm.201900950
|View full text |Cite
|
Sign up to set email alerts
|

Electro–Chemo–Mechanical Issues at the Interfaces in Solid‐State Lithium Metal Batteries

Abstract: Effective solid‐state interfacial contact of both the cathode and lithium metal anode with the solid electrolyte (SE) are required to improve the performance of solid‐state lithium metal batteries (SSBs). Electro–chemo–mechanical coupling (ECMC) strongly affects the interfacial stability of SSBs. On one hand, mechanical stress strongly influences interfacial contact and causes side reactions. On the other hand, electrochemical reactions such as lithium deposition cause mechanical deformation and stress at elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 208 publications
0
105
0
Order By: Relevance
“…[ 1 ] Among the prevalent ASSBs, poly(ethylene oxide) (PEO)‐based ASSB is one of the most practical battery system, [ 2 ] as the PEO‐based solid polymer electrolytes (SPEs) possess numerous merits in terms of high ionic conductivity, high processing ability, low cost, and acceptable stability against lithium metal. [ 3 ] Despite some early studies showing the stabilization of PEO‐SPEs to 4.2 V (versus Li/Li + ), [ 4 ] subsequent investigations have indicated that the reported “wide electrochemical window (EW)” is actually caused by kinetic polarization. [ 5 ] Xia et al firstly examined the EW of PEO‐SPEs by performing linear sweep voltammetry (LSV) measurements with carbon composite electrodes, and found that the oxidation of PEO‐SPEs started to occur at around 3.8 V. [ 5 ] Such restricted upper voltage limit was further confirmed by a sudden degradation of cycle life when the cut‐off charging voltage was increased to above 3.9 V. [ 6 ] Therefore, the widely reported PEO‐based ASSBs can only employ cathodes with low lithium storage potentials, for example V 2 O 5 [ 7 ] and LiFePO 4 , [ 8 ] as the capacity fades rapidly when PEO is paired with high voltage cathodes of above 3.9 V (e.g., LiCoO 2 , LiNi x Co y Mn 1‐ x ‐ y O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Among the prevalent ASSBs, poly(ethylene oxide) (PEO)‐based ASSB is one of the most practical battery system, [ 2 ] as the PEO‐based solid polymer electrolytes (SPEs) possess numerous merits in terms of high ionic conductivity, high processing ability, low cost, and acceptable stability against lithium metal. [ 3 ] Despite some early studies showing the stabilization of PEO‐SPEs to 4.2 V (versus Li/Li + ), [ 4 ] subsequent investigations have indicated that the reported “wide electrochemical window (EW)” is actually caused by kinetic polarization. [ 5 ] Xia et al firstly examined the EW of PEO‐SPEs by performing linear sweep voltammetry (LSV) measurements with carbon composite electrodes, and found that the oxidation of PEO‐SPEs started to occur at around 3.8 V. [ 5 ] Such restricted upper voltage limit was further confirmed by a sudden degradation of cycle life when the cut‐off charging voltage was increased to above 3.9 V. [ 6 ] Therefore, the widely reported PEO‐based ASSBs can only employ cathodes with low lithium storage potentials, for example V 2 O 5 [ 7 ] and LiFePO 4 , [ 8 ] as the capacity fades rapidly when PEO is paired with high voltage cathodes of above 3.9 V (e.g., LiCoO 2 , LiNi x Co y Mn 1‐ x ‐ y O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the fundamentals of ASSBs were reviewed by several authors [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The number of reviews on various aspects of electrolytes, cathodes, mechanical properties, and interface engineering has grown exponentially since 2018 [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ...…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chemical/electrochemical stability is another important requirement for SEI. Strong chemical/electrochemical stability represents nearly no side reactions and dendrites free at SEI 82. Side reactions at the interface would lead to high internal resistance and serious zinc dendrites.…”
Section: Fundamentals Of the Polymer Electrolytesmentioning
confidence: 99%